2022
DOI: 10.1007/jhep09(2022)127
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Carrollian gravity from the Carroll algebra

Abstract: We explicitly establish the equivalence between the magnetic Carrollian limit of Einstein gravity defined through the Hamiltonian formalism and the Carrollian theory of gravity defined through a gauging of the Carroll algebra along the lines of standard Poincaré (or (A)dS) gaugings.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Some of the models we construct in this way are new to the best of our knowledge and we give some preliminary analysis of their physical significance. It would be very interesting to extend our analysis to gravity, possibly producing new non-Lorentzian gravitational models beyond the ones already known [8,10,14,25,27,36,37].…”
Section: Introduction and Summary Of The Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the models we construct in this way are new to the best of our knowledge and we give some preliminary analysis of their physical significance. It would be very interesting to extend our analysis to gravity, possibly producing new non-Lorentzian gravitational models beyond the ones already known [8,10,14,25,27,36,37].…”
Section: Introduction and Summary Of The Resultsmentioning
confidence: 99%
“…This is motivated by their relevance to many physical situations in e.g. applications to condensed matter physics [4,5], hydrodynamics [6][7][8] and gravitational problems [9][10][11][12][13][14]. They have also featured prominently in non-relativistic variants of holography [15][16][17].…”
Section: Introduction and Summary Of The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One is by gauging the Carrollian algebra [58][59][60], and the other is by using the contraction of Lorentz theory [28]. A comparison between the magnetic theory from Carrollian contraction and the construction from gauge procedure were made in [61], while the electric sector is missing in the gauging description. The Bargmann reduction may shed light on this subtle issue, as it could in principle lead to both the electric and magnetic sectors at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been recently shown that the Hamiltonian formulation of general relativity admits at least two Carroll limits [21]. The so-called magnetic case is equivalent to the Carroll theory of gravity, defined through a gauging of the Carroll algebra [22].…”
Section: Introductionmentioning
confidence: 99%